Synthesis of Zeolite-X Supported on Kapok Fiber for CO2 Capture Material: Variation of Immersion Time during Fiber Activation - Mada Mariana Lakapu; Nurul Widiastuti (Indonesian Journal of Chemistry, 2017)
Zeolite-X is a potential material for CO2 adsorption. To increase the performance of zeolite-X, kapok fiber was used as a support material. The growth of zeolite-X on the surface of kapok was affected by activation of the surface. This research aims to optimize the immersion time of kapok fiber using NaOH in order to achieve high crystallinity of the zeolite-X. The Zeolite-X supported on kapok fiber was synthesized by the simple hydrothermal method at immersion time variation of 12 to 36 h. XRD results show that zeolite-X on kapok surface has the highest crystallinity at immersion time of 24 h. The topography of kapok surface from AFM indicates that the surface was damaged due to peeling reaction of NaOH. SEM results show that zeolite-X has grown on the kapok surface in considerable amounts. From TGA analysis, it was shown that the thermal stability of zeolite-X supported on kapok surface was up to 300 °C. Adsorption of CO2 measured by gravimetric method shows that CO2 adsorption capacitywas up to 15.097 wt.% at room temperature.